2017
DOI: 10.1186/s12906-017-2051-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety incident reports related to traditional Japanese Kampo medicines: medication errors and adverse drug events in a university hospital for a ten-year period

Abstract: BackgroundKampo medicine is traditional Japanese medicine, which originated in ancient traditional Chinese medicine, but was introduced and developed uniquely in Japan. Today, Kampo medicines are integrated into the Japanese national health care system. Incident reporting systems are currently being widely used to collect information about patient safety incidents that occur in hospitals. However, no investigations have been conducted regarding patient safety incident reports related to Kampo medicines. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The data reported in previous reports show that up to 56% of ADEs were attributed to MEs ( Bates et al, 1995a , Kunac and Tatley, 2011 , Tanti et al, 2013 ). A Japanese study reported that of all the 103 ADE cases that received traditional Japanese Kampo medication in one hospital, 99 were MEs and only 4 were ADRs ( Shimada et al, 2017 ). These studies prove the crucial role of MEs in ADEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data reported in previous reports show that up to 56% of ADEs were attributed to MEs ( Bates et al, 1995a , Kunac and Tatley, 2011 , Tanti et al, 2013 ). A Japanese study reported that of all the 103 ADE cases that received traditional Japanese Kampo medication in one hospital, 99 were MEs and only 4 were ADRs ( Shimada et al, 2017 ). These studies prove the crucial role of MEs in ADEs.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Zafar et al, established a streamlined interface design technique to improve the reporting rates of ADEs and MEs in the USA ( Zafar et al, 2008 ). Currently, several studies use the spontaneous reporting system to investigate MEs and ADRs in ADE in New Zealand ( Kunac and Tatley, 2011 ), Japan ( Shimada et al, 2017 ), the USA ( Carnovale et al, 2018 ), and Germany ( Koberle et al, 2018 ). All these reports agreed that the direct use of data from the spontaneous reporting system in the pharmacovigilance center to detect MEs and ADRs is convenient method.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, kampo medicine is integrated into Japan's national health management system. The Ministry of Health, Labour, and Welfare has approved 147 herbal medicinal extract formulations and one herbal medicinal ointment, along with 187 crude kampo drugs, which are used in the National Health Insurance program . Kamikihito ( Jia‐Wei‐Gui‐Pi‐Tang ; KKT) is a kampo extract formulation containing 14 crude drugs: Ginseng Radix, Atractyloides Rhizoma, Poria, Bupleuri Radix, Zizyphi Semen, Longan Arillus, Astragali Radix, Angelicae Radix, Gardeniae Fructus, Polygalae Radix, Zizyphi Fructus, Glycyrrhizae Radix, Sanssureae Radix, and Zingiberis Rhizoma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Kampo medicine is different from traditional Chinese and Korean medicines [ 3 ]. In Japan, Kampo medicines are integrated into the national health care system; 148 Kampo extract formulations and 187 types of crude drugs are approved by the Ministry of Health, Labour and Welfare and are used under the national health insurance programme [ 4 , 5 ]. Kampo medications are available over the counter (OTC) and are the most frequently used complementary and alternative medicine therapies in Japan according to surveys of Japanese physicians [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the common prescription of Kampo medications by Japanese physicians, there are no standard education programmes in medical schools and few postgraduate education programmes on Kampo medicines in Japan [ 3 , 10 , 11 ]. Given that a recent Japanese study reported some concerns regarding patient safety in relation to Kampo medications [ 4 ], it is important to ascertain the safety of the Kampo medications prescribed by physicians. Furthermore, given that adverse drug events are common in elderly patients due to multi-morbidity and polypharmacy [ 12 15 ], the appropriate use of Kampo medications by elderly patients is particularly important.…”
Section: Introductionmentioning
confidence: 99%